The impact of the use of the modified learning cycle strategy in the achievement of the students of the third grade in mathematics (A quasi-experimental study in Jablah city) - Hamdan, Maisaa; Alhafi, Rana (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The study aimed to detect the impact of the modified learning cycle strategy on the achievement of the students in the third grade. The quasi-experimental method was used. So, a learning program was designed according to the modified learning cycle strategy of the geometric unit from the mathematics book for the third grade. An achievement test that included (19) questiones divided into three sections: part as a multiple choice, part as spaces and short answers and part as geometric shapes was designed. The learning program was applied on sample of the third grade students of primary education. They were (72) students. The study showed that there is a statistic significant difference between the mediates grades of the two groups students (experimental and control) in the post and deferred application of the achievement test. This difference benefit the students of the experimental group. The study recommended the importance of applying the modified learning cycle strategy in teaching new curricula, and do studies that explore the impact of this strategy on the development of different thinking skills and in all subjects.